2021
DOI: 10.1177/14759217211009217
|View full text |Cite
|
Sign up to set email alerts
|

Condition identification of bolted connections using a virtual viscous damper

Abstract: Vibration-based condition identification of bolted connections can benefit the effective maintenance and operation of steel structures. Existing studies show that modal parameters are not sensitive to such damage as loss of preload. In contrast, structural responses in the time domain contain all the information regarding a structural system. Therefore, this study aims to exploit time-domain data directly for condition identification of bolted connection. Finite element model updating is carried out based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…To evaluate the performance of the proposed method in such a situation, this study will use numerical simulation data as the source domain data and laboratory test data as the target domain, referred to as case 2 thereafter. In this case, calibrated FE and state-space models are employed to generate time-domain vibration responses of the prototype structure that match the actual test data almost precisely [20]. Te results demonstrate the similarity of the data between the source domain and target domain, so the negative transfer can be avoided.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…To evaluate the performance of the proposed method in such a situation, this study will use numerical simulation data as the source domain data and laboratory test data as the target domain, referred to as case 2 thereafter. In this case, calibrated FE and state-space models are employed to generate time-domain vibration responses of the prototype structure that match the actual test data almost precisely [20]. Te results demonstrate the similarity of the data between the source domain and target domain, so the negative transfer can be avoided.…”
Section: Methodsmentioning
confidence: 98%
“…For each accelerometer, a total of 110 sets of structural responses were recorded. Tese datasets were not only used to construct SHMnet and to perform the two-stage model updating [20] but also as the training data source for the present study. More details on the experimental works can be found in [24].…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Viscous fluid damper is a passive control device (Biswal et al, 2022; Khedmatgozar Dolati et al, 2021; Rajeswaran and Wijeyewickrema, 2022; Zhou et al, 2016). Its basic principle is that the fluid inside the damper generates throttling resistance through a specific hole or device clearance and then dissipates the energy input to the damper from the outside.…”
Section: Introductionmentioning
confidence: 99%
“…Montalva et al [24] conducted a study on how the damage level affects the damping in carbon fiber-reinforced laminates and concluded that the damping always increases overall with damage, but the individual variation of the modal damping factor is very uncertain. Biswal et al [25] proposed a virtual damper concept to update the system matrix of the finite element model, and the results show that the virtual damper is not only effective in estimating the time-domain response but also has the potential for condition identification of the bolted connection.…”
Section: Introductionmentioning
confidence: 99%